Generation of wideband electromagnetic radiation on a decay stage of a mirror-confined plasma produced by ECR discharge - Shalashov, A.G.; Golubev, S.V.; Gospodchikov, E.D.; Mansfeld, D.A.; Viktorov, M.E.; Vodopyanov, A.V. (Вопросы атомной науки и техники, 2013)
A specific nonlinear regime of electron cyclotron instability is discussed aimed at explanation of complex temporal patterns of stimulated electromagnetic radiation from a mirror trap with non-equilibrium plasma typical of ECR discharge. This regime is characterized by self-modulation of a plasma cyclotron maser due to coherent interference of two counter-propagating unstable waves with degenerate frequencies. The proposed simple theoretical model allows reproducing multi-scale behavior of quasi-periodic pulses of electromagnetic radiation and precipitation of energetic electrons detected at a laboratory setup based on a mirror trap with plasma sustained by mm-wave gyrotron radiation. Обсуждается новый нелинейный режим электронно-циклотронной неустойчивости, объясняющий сложную временную динамику импульсов электромагнитного излучения сильнонеравновесной плазмы ЭЦР-разряда в прямой магнитной ловушке. Режим реализуется при самомодуляции циклотронного мазера полем биений двух встречных неустойчивых волн с вырожденными частотами. Предложенная простая теоретическая модель позволяет воспроизвести многомасштабную структуру импульсов электромагнитного излучения и высыпания энергичных электронов, зарегистрированных в лабораторном эксперименте с использованием прямой ловушки с плазмой, поддерживаемой излучением гиротрона миллимeтрового диапазона. Обговорюється новий нелінійний режим електронно-циклотронної нестійкості, що пояснює складну часову динаміку імпульсів електромагнітного випромінювання сильнонеравномірної плазми ЕЦР-розряду в прямій магнітній пастці. Режим реалізується при самомодуляціі циклотронного мазера полем биття двох зустрічних нестійких хвиль з виродженими частотами. Запропонована проста теоретична модель дозволяє відтворити багатомасштабну структуру імпульсів електромагнітного випромінювання та висипання енергійних електронів, зареєстрованих у лабораторному експерименті з використанням прямої пастки з плазмою, що підтримується випромінюванням гіротрона миллиметрового діапазону.